Translating Jazz Into Poetry - Redling, Erik (De Gruyter, 2017)
The study develops a new theoretical approach to the relationship between two media (jazz music and writing) and demonstrates its explanatory power with the help of a rich sampling of jazz poems. Currently, the mimetic approach to intermediality (e.g., the notion that jazz poetry imitates jazz music) still dominates the field of criticism. This book challenges that interpretive approach. It demonstrates that a mimetic view of jazz poetry hinders readers from perceiving the metaphoric ways poets rendered music in writing. Drawing on and extending recent cognitive metaphor theories (Lakoff, Johnson, Turner, Fauconnier), it promotes a conceptual metaphor model that allows readers to discover the innovative ways poets translate
10.1515/9783110339017
Keywords: Poetry / History and criticism; American Literature; Amerikanische Literatur; Cognitive Poetics; Intermediality; Intermedialität; Jazz Music; Jazz-Musik; Kognitive Poetik; Jazz; Jazz poetry; LITERARY CRITICISM / American / General